Malaysian Consumer Intention toward Takaful Scheme for Mental Health Disorders - Khairil Faizal Khairi; Nur Hidayah Laili; Aimi Fadzirul Kamarubahrin (Journal of Finance and Islamic Banking, 2020)
This paper investigates the factors influencing Malaysian consumer intention toward takaful scheme for mental health disorders. An applied expanded Theory of Reasoned Action (TRA) model were used in the research and the variables of awareness, perception, attitude, subjective norm and intention toward a takaful scheme for mental health disorders were investigated. It is a pilot research carried out in Malaysia. The respondents are 60 Malaysian takaful consumers based on an online survey inside Klang Valley, Malaysia. This study reveals that the mean of attitude with the score of 4.27 is the highest score. The Pearson correlation is positive for both independent and dependent variables. Analysis of regression indicates a strong positive relationship between subjective norm and intention, thus suggesting that subjective norm is an important area to link to intention against mental health disorder takaful scheme. This is also proposed that future studies will concentrate on the factors that affect the willingness of consumers towards takaful mental health disorder schemes. It is hoped that the results of this study will serve as an informative reference for further development of takaful scheme for mental health disorder.